Automated System for Generating and Evaluating Tests - S. A. Migalevich; O. V. German (Цифровая трансформация)
The importance of knowledge testing in the educational process and its role in identifying gaps in students’ knowledge and modernizing education are noted. The contextual links between the concept of quality and educational testing, the representation of knowledge about the subject area using the Martynov triad are considered. The main focus is on the semantic web, where concepts represent testable knowledge elements. Concepts are classified into different types depending on the information they contain, such as general textual concept, list/classification/hierarchy, program code, formulaic concept, causal concept, and others. The generation of test questions is considered, the QueTabAI system is described, which automatically generates questions based on the presented knowledge about the subject area. Methods for generating questions with their compilation on the basis of grammatical analysis of the text are given. The signs or criteria that are identified through testing are listed. Various aspects and methods of feature formation are studied, allowing to make a decision on the need to fill in the knowledge gaps and modernize the educational process.